Do corruption and economic growth lead to income inequality in Indonesia? / Ahmad Shahsufian Sani - Sani, Ahmad Shahsufian (Faculty of Business and Management, 2020)
The objective of the present study is to examine the factor that most affected-on income inequality in Indonesia for the period between 1984 and 2017 using times series framework. To answer 3 objectives under this investigation, through ARDL method. Gross domestic product per capita, corruption, foreign direct investment and trade openness are having significant relationship towards inequality, while inflation shows otherwise. This study is conducted by using time series analyses by utilizing the Autoregressive Distributive Lag (ARDL) techniques. Overall, based on the result driven from the long run coefficient analysis, the gross domestic product, foreign direct investment and trade openness has negative relationship which mean an increase in the variables, the inequality of income distribution may decrease while for the corruption is vice versa.